Deciding Who Is Worthy of Help: Effect of the Probability of Reciprocity on Individuals’ Willingness to Help Others - Ryo Oda; Natsuki Hayashi (Evolutionary Psychology, 2024)
In order to explain helping strangers in need in terms of reciprocal altruism, it is necessary to ensure that the help is reciprocated and that the costs of helping are thus compensated. Competence and willingness to make sacrifices for the benefactor of the person being helped are important cues for ensuring a return on help because reciprocity would not be possible if the person being helped had neither the competence nor the inclination to give back in the future. In this study, we used vignettes and manipulated the cause of suffering strangers’ difficulties and prosociality to investigate participants’ compassion for and willingness to help the stranger. In Study 1, we measured willingness to help by using hypothetical helping behaviors that were designed to vary in cost. In Study 2, we measured willingness to help by using the checkbox method in which participants were asked to sequentially check 10 × 10 checkboxes on a webpage, which asked the participants to pay a small but real cost. In both studies, the controllability of the cause and the prosociality were found to independently affect compassion. These two factors also independently affected willingness to help, as measured by both the hypothetical questions and the checkbox method. We consequently discussed the reasons for the independent processing of the competence and behavioral tendency cues.